Analysis of Diagenetic Evolution and Pore Structure Response Mechanism of Low Permeability Sandstone Reservoir in Chang 6 Member of Yanchang Formation - Liu, Kaixuan; Wang, Jiangtao (International Journal of Natural Resources and Environmental Studies, 2025)
The low permeability sandstone reservoir in Chang 6 member of Yanchang Formation in Ordos Basin is one of the important oil-bearing strata in China, but its low permeability characteristics pose a great challenge to oil and gas exploitation. In this paper, the diagenetic evolution process and pore structure characteristics of low permeability sandstone reservoirs in Chang 6 member of Yanchang Formation are systematically analyzed, and the response mechanism between diagenesis and pore structure is discussed. The research results show that the sandstone reservoir in Chang 6 member has experienced complex diagenesis, including mechanical compaction, cementation and dissolution, which are intertwined and have a profound impact on the pore structure of the reservoir. Compaction makes particles closely arranged and reduces porosity; Cementation further blocks pores and throats, significantly reducing permeability; However, dissolution forms secondary pores by dissolving some minerals, which improves reservoir physical properties to some extent. In the process of diagenetic evolution, the pore types gradually changed from primary macropores to micropores and nanopores, and the pore throat structure showed the evolution characteristics of "fine granularity", which led to the decrease of reservoir permeability. In addition, dissolution has a double effect of "compensation-limitation". Although it can generate secondary pores to improve permeability, dissolution products often re-precipitate in the form of authigenic minerals, which inhibits the further expansion of pores. The study shows that the balance of "destruction-filling" dominated by compaction-cementation and the double effect of dissolution are the key factors leading to the low permeability characteristics of reservoirs.